A methods engineering study on 4M Furniture Store - Balagtas, Paula Marie L. (College of Engineering, 2001)
4M Furniture Store is a medium-scale production system mass-producing fully upholstered sofa sets. This methods engineering study on M Furniture Store aims to increase the efficiency and labor productivity of the plant by addressing the main problem, which is determined through the use of problem analysis tools. The identified problem is the efficiency of the plant layout. Alternative solutions are then generated and evaluated to determine the best recommendations that will solve the inefficiency of the plant layout. The factors considered in the evaluation of the generated alternatives are cost, ability to improve present condition, ease of implementation, safety and possibility of accomplishment. The group presented three layout alternatives to address the main problem : layout without purchase of land and without costly renovations, layout without purchase of land but with costly renovations and layout with purchase of land. The second alternative is recommended along with other methods improvements such as : adaptation of the perpetual inventory system, scrap segregation, and introduction of SOPs and standard time. These recommendations are projected to decrease the total distance traveled by a worker to produce one sofa set by at least 26 percent. Consequently, there will be a decrease in total time to manufacture one sofa set, hence an increase in labor productivity and efficiency of the plant.